2022
DOI: 10.3390/molecules27217296
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces rochei MS-37 as a Novel Marine Actinobacterium for Green Biosynthesis of Silver Nanoparticles and Their Biomedical Applications

Abstract: Periodontitis, as one of the most common diseases on a global scale, is a public health concern. Microbial resistance to currently available antimicrobial agents is becoming a growing issue in periodontal treatment. As a result, it is critical to develop effective and environmentally friendly biomedical approaches to overcome such challenges. The investigation of Streptomyces rochei MS-37’s performance may be the first of its kind as a novel marine actinobacterium for the green biosynthesis of silver nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Silver NPs synthesized from Actinobacteria obtained from the marine ecosystem were proven to be effective in periodontitis. On testing, it proved to suppress infection, reduce inflammation, anti-denaturation effect, and high cytotoxicity [ 24 ]. A microtiter-dilution resazurin test was used to assess the antibacterial efficacy of NP alone and in conjunction with antibiotics against multidrug-resistant (MDR) bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver NPs synthesized from Actinobacteria obtained from the marine ecosystem were proven to be effective in periodontitis. On testing, it proved to suppress infection, reduce inflammation, anti-denaturation effect, and high cytotoxicity [ 24 ]. A microtiter-dilution resazurin test was used to assess the antibacterial efficacy of NP alone and in conjunction with antibiotics against multidrug-resistant (MDR) bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A microtiter-dilution resazurin test was used to assess the antibacterial efficacy of NP alone and in conjunction with antibiotics against multidrug-resistant (MDR) bacteria. It was found to have a synergistic effect [ 24 , 25 ]. ZnONPs have remarkable and incredible properties.…”
Section: Discussionmentioning
confidence: 99%
“…Most isolated bacteria from burn patients frequently develop biofilms on the ulcerated sections of burn wounds [ 4 ]. Microorganisms have created a variety of strategies to counter antimicrobial drugs, such as reducing cellular permeability to decrease drug penetration, enzymatically breaking down antimicrobial compounds, and forming biofilms [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, MDR bacteria cause serious infections as a result of bacterial adaptation that includes the development of mutations, transformation, conjugation, transposition, and transduction [ 21 ]. Increasing MDR has generated scientific interest to discover novel antimicrobial agents with broad spectrum activities to complement and/or replace conventional antibiotics [ 5 , 15 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant examples are the polyketide antibiotics lankacidin and lankamycin from S. rochei 7434AN4 [10,11], the new metabolites from the coculture of the marine-derived actinobacterium Streptomyces rochei MB037 and the fungus Rinocladiella similis 35 [12]. Furthermore, it was reported that the marine-derived S. rochei MHM13 and S. rochei MS-37 have the ability to synthesize silver nanoparticles, exhibiting a wide range of inhibition against both Gram-positive and -negative bacteria [13,14]. Additionally, enzymes with biotechnological interest [15,16] are produced by a new soil-derived Streptomyces rochei subsp.…”
Section: Introductionmentioning
confidence: 99%